The impact of sensitive KIT D816V detection on recognition of Indolent Systemic Mastocytosis. Issue 3 (March 2015) - De Matteis, Giovanna; Zanotti, Roberta; Colarossi, Sabrina; De Benedittis, Caterina; Garcia-Montero, Andrès; Bonifacio, Massimiliano; Sartori, Marta; Aprili, Fiorenza; Caruso, Beatrice; Paviati, Elisa; Carli, Giuseppe; Perbellini, Omar; et al.
Highlights Indolent Systemic Mastocytosis is characterized by a very low mast cell burden. We describe the impact of a highly sensitive test for D816V detection. We tested BM cells in 110 consecutive patients with suspicion. We believe that ARMS-RTq-PCR technique has a remarkable impact for the diagnosis.